2021
DOI: 10.1177/1420326x211012431
|View full text |Cite
|
Sign up to set email alerts
|

Thirdhand smoke exposure: Differences in smoke exposure indices and cultural norms between hotels and motels in South Korea

Abstract: The legal regulations and cultural environment for smoking bans in hotels and motels in South Korea differ depending on the type of accommodation. The aim of this study was to assess the thirdhand smoke exposure for hotel and motel guests staying at accommodations who are expected to be relatively vulnerable to thirdhand smoke. Biomarkers for 28 participants were assessed before and after lodging at a hotel or motel for approximately 14 h. Hotel participants had statistically decreased urinary cotinine concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Thirdhand smoke is when an individual is exposed to substances released to the air after being absorbed into the smoker's body, clothes, walls, or curtains, even if they are not exposed to the cigarette smoke caused by others. Recent studies have reported increased urine cotinine due to thirdhand smoke, even when not exposed to secondhand smoke [26][27][28] . Second, self-report cannot measure exposure in all settings.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdhand smoke is when an individual is exposed to substances released to the air after being absorbed into the smoker's body, clothes, walls, or curtains, even if they are not exposed to the cigarette smoke caused by others. Recent studies have reported increased urine cotinine due to thirdhand smoke, even when not exposed to secondhand smoke [26][27][28] . Second, self-report cannot measure exposure in all settings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, interest in thirdhand smoke (THS) has grown in recent years. THS refers to exposure to indirect smoking through tobacco residue that is adsorbed into surfaces within an environment and is re-emitted to the individual remaining in the same space afterward [18,19]. Studies have reported that individuals in these circumstances do not recognize tobacco smoke, and even short-term exposure through THS can elevate cotinine concentrations in the body [20].…”
Section: Measurement Of the Prevalence Of Active And Passive Smokingmentioning
confidence: 99%
“…THS poses a health risk by altering and destroying the DNA structure [10], increasing the incidence of cancer in nonsmokers [11], and emitting the same toxic substances as SHS [12]. Cotinine and nicotine concentrations reportedly increase among individuals who spend time in places in which smoking was likely to have occurred, such as places of accommodation, rental cars, and used cars [13][14][15][16]. Nonsmokers living with a smoker (even if SHS does not occur within the house) reportedly exhibit a high urine cotinine concentration [17].…”
Section: Introductionmentioning
confidence: 99%